HARGA MINYAK DAN PERTUMBUHAN EKONOMI DI INDONESIA PERIODE 1984-2014 - Sultan, Sultan; Soesilo, AM. (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2017)
Oil Price and Economic Growth in Indonesia Period 1984-2014. Oil prices and economic growth are important indicators for the performance of a country's development in terms of natural resources. This study aims to test and create empirical evidence of a two-way relationship of influence between oil prices and economic growth in Indonesia: (1) Effect of oil prices, non-oil consumption and mining sector investment on economic growth. (2) Effect of economic growth, and non-oil consumption on oil prices. This study uses time series data from 1984-2014. The method used is descriptive and econometric approach of simultaneous equation model analysis with two stages of least squares method (Two Stage Least Square / 2SLS). The results show that there is a two-way relationship between oil prices and economic growth. Economic growth and non-oil consumption have a significant effect on oil prices. Similarly, oil prices and mining sector investment have a positive effect on economic growth, while non-oil consumption negatively affected the growth of economists in Indonesia during the period of study 1984-2014